Trends in Multicultural Education Publication Over a Four-Decade Period: A Bibliometric Review - Roni Rodiyana; Bunyamin Maftuh; Sapriya Sapriya; Ernawulan Syaodih; Davi Sofyan (Al Ibtida: Jurnal Pendidikan Guru MI, 2022)
AbstractThe objective of this study is to systematically review academic works in the area of multicultural education. Publications were gathered using the Scopus database and a variety of bibliometric variables. The publishing mapping program VOS viewer was used to analyzing the collected data. There were 501 publications on intercultural and multicultural education that were published between 1973 to 2021. The results showed that between 1973 and 2021, the number of publications varied. With the addition of 12 publication documents, the number of publications has doubled starting in 1997. The most published documents amounted to 42 in 2020. The number of academic scientific papers published in the United States, which is recognized as the most productive nation, is 321. Constantine, M.G., of Columbia University in the United States, is the most prolific writer. With 14 publications, Columbia University in the US was the most productive university. The findings of this study imply that the main keyword is "multicultural training" which is grouped with "case conceptualization", "multicultural case conceptualization", "multicultural competency", "school psychology", and "supervision". This indicates that the topic of multicultural education is closely related to the keywords, and future researchers should investigate these keywords to have a deeper understanding of the field of multicultural education.Keywords: multicultural education, bibliometric review, publication trends, VOS viewerAbstrakPenelitian ini bertujuan untuk meninjau secara sistematis karya akademis di bidang pendidikan multikultural. Publikasi dikumpulkan menggunakan database Scopus dan berbagai variabel bibliometrik. Program pemetaan penerbitan VOSviewer digunakan untuk menganalisis data yang dikumpulkan. Ada 501 publikasi tentang pendidikan antar budaya dan multukultural yang ditemukan antara tahun 1973 hingga 2021. Hasil penelitian menunjukkan bahwa antara tahun 1973 hingga 2021, jumlah publikasi bervariasi. Dengan tambahan 12 dokumen publikasi jumlah publikasi menjadi dua kali lipat mulai tahun 1997. Dokumen paling banyak diterbitkan berjumlah 42 pada tahun 2020. Jumlah karya ilmiah akademik yang diterbitkan di Amerika Serikat, yang diakui sebagai negara paling produktif sebanyak 321 dokumen. Constantine, M.G., dari Universitas Columbia di Amerika Serikat, adalah penulis paling produktif. Dengan 14 publikasi, Universitas Columbia di AS adalah universitas paling produktif. Temuan penelitian ini menyiratkan bahwa kata kuncinya adalah "pelatihan multikultural", yang dikelompokkan dengan "konseptualisasi kasus", "konseptualisasi kasus multikultural", "kompetensi multikultural", "psikologi sekolah", dan "pengawasan". Hal ini menunjukkan bahwa topik pendidikan multikultural berkaitan erat dengan kata kunci yang dikemukakan, dan peneliti selanjutnya harus menyelidiki kata kunci tersebut agar memiliki pemahaman yang lebih mendalam tentang bidang pendidikan multikulturalKata kunci: pendidikan multikultural, tinjauan bibliometrik, tren publikasi, VOS viewer